Analysis of parental awareness regarding the role of Art Therapy in the development of children with complex multiple disabilities - Muradyan, Svetlana; Gabrielyan, Amalya
Emphasizing the need to develop the creative abilities of children with complex, multiple disabilities, within the full implementation of the educational process, both at home and in school, the need to raise the level of awareness of parents in regards the issues under study is greatly emphasized. This article analyzes the level of awareness of parents about the developmental role of art therapy, the existing problems, as well as the concerns parents have. In the frame of the current research the quantitative research is use for collecting and analyzing numerical data. It is called to make predictions, and generalize results to wider populations. The results of the presented research prove the role of the parent, and the family in general in the further development of the child, ensuring the full-fledged educational process. In this context, it is considered extremely important to ensure the level of awareness of parents about the current approaches to the implementation of the educational process of children and their further development.
Keywords: Psychology